Advancing environmental monitoring across the water continuum combining biomarker analysis in multiple sentinel species: A case study in the Seine-Normandie Basin (France) - Sylvain Slaby; Alain Geffard; Cédric Fisson; Matthieu Bonnevalle-Normand; Anne-Sophie Allonier-Fernandes; Rachid Amara; Anne Bado-Nilles; Isabelle Bonnard; Marc Bonnard; Mayélé Burlion-Giorgi; Amélie Cant; Audrey Catteau; et al. (Journal of Environmental Management, 2024)

The lifecycle of volcanic ash: advances and ongoing challenges - Joali Paredes-Mariño; Pablo Forte; Stefano Alois; Ka Lok Chan; Valeria Cigala; Sebastian B. Mueller; Matthieu Poret; Antonio Spanu; Ines Tomašek; Pierre-Yves Tournigand; Diego Perugini; Ulrich Kueppers (Bulletin of Volcanology, 2022)
Explosive volcanic eruptions can produce vast amounts of volcanic ash made up mainly of fragments of magmatic glass, country rock and minerals < 2 mm in size. Ash particles forming from magma fragmentation are generated by several processes when brittle response accommodates (local) deformation stress that exceeds the capability of the bulk material to respond by viscous flow. These processes span a wide range of temperatures, can occur inside or outside the volcanic edifice and can involve all melt compositions. Ash is then dispersed by volcanic and atmospheric processes over large distances and can have global distributions. Explosive eruptions have repeatedly drawn focus to studying volcanic ash. The continued occurrence of such eruptions worldwide and their widespread impacts motivates the study of the chemical and physical processes involved in the lifecycle of volcanic ash (e.g. magma fragmentation, particle aggregation), as well as the immediate to long-term effects (e.g. water and air pollution, soil fertilization) and consequences (e.g. environmental, economic, social) associated with ashfall. In this perspectives article, we reflect on the progress made over the last two decades in understanding (1) volcanic ash generation; (2) dispersion, sedimentation and erosion; and (3) impacts on the atmosphere, hydrosphere, biosphere and modern infrastructure. Finally, we discuss open questions and future challenges.

Total grain size distribution of an intense Hawaiian fountaining event: case study of the 1959 Kīlauea Iki eruption - Sebastian B Mueller; Bruce F Houghton; Donald A Swanson; Matthieu Poret; Sarah A Fagents (Bulletin of Volcanology, 2019)